Neurocysticercosis and Hippocampal Atrophy: MRI Findings and the Evolution of Viable or Calcified Cysts in Patients With Neurocysticercosis - Jama-António, Job Monteiro C.; Yasuda, Clarissa L.; Cendes, Fernando (Frontiers in Neurology, 2019)
Neurocysticercosis (NC) is the most common parasitic infection of the central nervous system (CNS). Several studies have reported an association between NC and mesial temporal lobe epilepsy (MTLE). We intended to evaluate the frequency of hippocampal atrophy (HA), clinical evolution and imaging findings in patients with calcified neurocysticercotic lesions (CNLs). Methods: One hundred and eighty-one subjects (70 cases and 111 controls) were evaluated for the presence or absence of HA. We assessed the imaging findings, and the evolution of patients with NC treated or not with anthelmintics for NC. Results: Hippocampal volumes were different between cases and controls (p < 0.001). Seventy percent of the cases presented HA. 52.2% of the patients without a history of anthelmintic treatment for NC had reports of epileptic seizures. There was an association between non-treatment and the later occurrence of epileptic seizures (p = 0.006). There was an association between perilesional edema on MRI and the presence of uncontrolled epileptic seizures (p = 0.004). Conclusions: Hippocampal atrophy is frequent in patients with NCC. There was an association between no anthelmintic treatment in the acute phase of NC, perilesional edema, more pronounced hippocampal atrophy, and the occurrence of refractory seizures.